Potent and selective inhibitors of 11β‐hydroxysteroid dehydrogenase type 1 labeled with carbon‐13 and carbon‐14. (14th June 2017) - Latli, Bachir; Hrapchak, Matt; Savoie, Jolaine; Zhang, Yongda; Busacca, Carl A.; Senanayake, Chris H.
Abstract : ( S )‐6‐(2‐Hydroxy‐2‐methylpropyl)‐3‐(( S )‐1‐(4‐(1‐methyl‐2‐oxo‐1, 2‐dihydropyridin‐4‐yl)phenyl)ethyl)‐6‐phenyl‐1, 3‐oxazinan‐2‐one (1) and (4a R, 9a S )‐1‐(1 H ‐benzo[d]midazole‐5‐carbonyl)‐2, 3, 4, 4a, 9, 9a‐hexahydro‐1‐ H ‐indeno[2, 1‐b]pyridine‐6‐carbonitrile hydrochloride (2) are potent and selective inhibitor of 11β‐hydroxysteroid dehydrogenase type 1 enzyme. These 2 drug candidates developed for the treatment of type‐2 diabetes were prepared labeled with carbon‐13 and carbon‐14 to enable drug metabolism, pharmacokinetics, bioanalytical, and other studies. In the carbon‐13 synthesis, benzoic‐ 13 C 6 acid was converted in 7 steps and in 16% overall yield to [ 13 C6 ]‐(1). Aniline‐ 13 C 6 was converted in 7 steps to 1 H ‐benzimidazole‐1‐2, 3, 4, 5, 6‐ 13 C 6 ‐5‐carboxylic acid and then coupled to a tricyclic chiral indenopiperidine to afford [ 13 C6 ]‐(2) in 19% overall yield. The carbon‐14 labeled (1) was prepared efficiently in 2 radioactive steps in 41% overall yield from an advanced intermediate using carbon‐14 labeled methyl magnesium iodide and Suzuki‐Miyaura cross coupling via in situ boronate formation. As for the synthesis of [ 14 C]‐(2), 1 H ‐benzimidazole‐5‐carboxylic‐ 14 C acid was first prepared in 4 steps using potassium cyanide‐ 14 C, then coupled to the chiral indenopiperidine using amide bond formation conditions in 26% overall yield. Abstract : ( S )‐6‐(2‐Hydroxy‐2‐methylpropyl)‐3‐(( S )‐1‐(4‐(1‐methyl‐2‐oxo‐1, 2‐dihydropyridin‐4‐yl)phenyl)ethyl)‐6‐phenyl‐1, 3‐oxazinan‐2‐one (1) and (4a R, 9a S )‐1‐(1 H ‐benzo[d]midazole‐5‐carbonyl)‐2, 3, 4, 4a, 9, 9a‐hexahydro‐1‐ H ‐indeno[2, 1‐b]pyridine‐6‐carbonitrile hydrochloride (2) are potent and selective inhibitor of 11β‐hydroxysteroid dehydrogenase type 1 enzyme. These 2 drug candidates developed for the treatment of type‐2 diabetes were prepared labeled with carbon‐13 and carbon‐14.